Design and Implementation of the IoT Surveillance System using Electronic Appliances with Raspberry Pi - Huda G. Alsaffar; Ergun Erçelebi (Al-Iraqia Journal for Scientific Engineering Research, 2025)
The importance of security and surveillance systems in today's society cannot be overstated. The monitoring system can send out early alerts in an emergency. This study investigates an IoT surveillance system that can detect movement, record video footage by the camera module in real-time, and count the recorded video footage. The video footage is sent to the user via Mail. In addition to sending notification messages, "WARNING! Motion is detected, and the video is sent to Gmail for playback" immediately to the mobile phone using the Telegram application via Wi-Fi (Wireless Fidelity). It is worth mentioning that the microcontroller for this system is the Raspberry Pi 3 Model B. Additionally, the Passive Infrared (PIR) sensor detects any movement by measuring the changes in Infrared (IR) radiation. The Light Dependent Resistor (LDR) sensor is also used to check whether daylight or darkness exists. Furthermore, if the movement is detected, the Light Emitting Diode (LEDs) and the Lightbulb will be lit up/down depending on the state of the Light Dependent Resistor (LDR) sensor. The buzzer will activate to provide the emergency sound, and a power bank will be used as a power source to avoid interruptions in electrical power for the surveillance system.